Traditional Chinese medicine residue cellulose-based antibacterial and absorbable medical suture and preparation method thereof
By isolating cellulose formate from the Chinese medicine residue and preparing adjustable cellulose medical sutures, the problem of inability to absorb and lack of antibacteriality of cellulose medical sutures is solved, and the true absorbable and antibacterial properties of cellulose medical sutures are achieved, which promotes wound healing.
Patent Information
- Application Number
- CN202510097002.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-18
AI Technical Summary
Existing cellulose medical sutures cannot be absorbed in the human body and lack antibacterial properties, which limits its application as a medical material.
Cellulose formate is isolated from the Chinese medicine residue, and cellulose medical sutures with adjustable ester group substitution and polymerization are prepared by low-temperature steam explosion treatment and formic acid esterification reaction. The suture degrades in vivo to absorbable glucose and has antibacterial properties.
The true absorbability and antibacterial properties of cellulose medical sutures have been achieved, and the problems of inabsorbability and lack of antibacterial properties of cellulose medical sutures in the prior art have been overcome. They have excellent biocompatibility and appropriate degradation time, which promotes wound healing.
Smart Images

Figure CN119838044A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, relates to the preparation and application of cellulose ester-based medical sutures, and specifically relates to absorbable medical sutures prepared from traditional Chinese medicine residues and applications thereof. Background Art
[0002] With the industrialization and scale of Chinese medicine production in my country, the main product forms of Chinese medicine have gradually increased, including decoction pieces, Chinese patent medicines, Chinese medicine formula granules, etc. In order to extract active ingredients from Chinese medicine, a large amount of cellulose solid residue will inevitably be produced. At present, my country produces more than 70 million tons of solid waste from Chinese medicine every year. How to solve the problem of the discharge and treatment of a large amount of drug residues is becoming one of the bottleneck problems restricting the development of the Chinese medicine pharmaceutical industry. The main treatment methods for traditional Chinese medicine residues are landfill, incineration, and stacking. However, due to the high water content of Chinese medicine residues and easy fermentation and corruption, the above treatment methods will not only waste land resources, but also cause air and land pollution. On the other hand, since most Chinese medicines have a single processing and extraction method and low utilization rate, their residues still have a high development and utilization value. Therefore, how to reasonably use Chinese medicine residues is a technical problem that needs to be solved in the development of Chinese medicine.
[0003] According to literature records, cellulose can be directly prepared into silk material and used as medical sutures. However, since there is no enzyme in the human body that can decompose cellulose, cellulose cannot be absorbed in the human body; therefore, pure cellulose silk can only be used as non-absorbable sutures. To solve this problem, researchers used modified nanocellulose and cationic guar gum to prepare medical sutures with excellent mechanical properties (tensile strength 178MPa) and suture operability. The cellulose suture first absorbs water and swells in the body, then loses strength and degrades into small-sized cellulose fragments. Although, according to the definition of absorbable medical sutures, the strength degradation rate of silk within 60 days of implantation in the body is greater than 50%, and the silk belongs to absorbable sutures (Small, 2023, 19(4): 2205867). But in fact, it is not comprehensive to only use strength loss to indicate the absorbability of sutures, because degradability does not mean that its degraded components are absorbable. Since nanocellulose is still essentially natural cellulose, it cannot be absorbed by human tissues in the body. Therefore, there is no report on truly absorbable medical sutures developed using cellulose raw materials. In addition, ordinary cellulose threads themselves do not have antibacterial properties and usually require the introduction of antibacterial agents or sterilization treatment, which not only leads to increased costs but also limits its feasibility as a medical material.
[0004] As we all know, Chinese medicine mainly comes from natural medicine and its processed products, mainly composed of botanicals, animal medicines and some mineral medicines, of which botanicals account for more than 87%. Based on this, the cellulose solid residue produced after extracting active ingredients from Chinese medicine - Chinese medicine residue, is rich in cellulose, lignin, hemicellulose and other components (Specialty Product Research, 2024: 1-7; Bioprocessing, 2019, 17(2): 171-176). At present, there is no report on the use of Chinese medicine residue to efficiently separate cellulose and prepare absorbable medical sutures after pretreatment. Summary of the invention
[0005] In view of the problems existing in the cellulose sutures in the prior art, the present invention provides an application of Chinese medicine residue-based cellulose formate as a medical suture, and a method for preparing antibacterial and absorbable cellulose medical sutures using Chinese medicine residue-based cellulose formate. The cellulose medical suture is truly absorbable, overcoming the technical prejudice of the prior art that cellulose is not absorbable, and producing unexpected technical effects. Not only that, the cellulose medical suture also has antibacterial properties, and its degradation properties can be adjusted, and the preparation process is gentle and clean, with broad market application prospects and huge economic value.
[0006] A use of cellulose formate based on Chinese medicine residue as a medical suture. The cellulose formate is separated from Chinese medicine residue; the ester substitution degree of the cellulose formate is 1.3-2.5, the crystal form is cellulose II type, and the degree of polymerization is 400-600. The Chinese medicine residue raw material is one or more of Astragalus, Codonopsis, Atractylodes, Angelica, Chuanxiong, Polygonatum, Dipsacus, Pueraria, Rhodiola, Salvia, Rehmannia and Coptis.
[0007] The inventor unexpectedly discovered in the research that, unlike the cellulose in the prior art, the cellulose formate mentioned above can be degraded into glucose that can be absorbed and utilized by human tissue in simulated body fluids, so it can be used as a truly absorbable medical suture, overcoming the technical bias in the prior art and achieving unexpected technical effects. The inventor found through research that this is because cellulose formate releases trace amounts of acid when it degrades in body fluids, forming a weak acid environment. This weak acid environment will further reduce the degree of polymerization of cellulose, thereby promoting the degradation of cellulose into glucose that can be absorbed and utilized by tissues.
[0008] At the same time, the inventors also found that the strength degradation rate and absorbability rate of the silk thread can be adjusted by the degree of substitution and degree of polymerization of esterified cellulose, so that the absorbability rate of the silk thread matches the wound tissue recovery cycle (for example, rat epidermal wound healing takes 5-7 days, while liver healing takes 14-28 days). It is well known that the strength degradation rate of absorbable sutures directly affects the effect of wound healing. If the degradation is too fast, the wound may not be completely closed, resulting in poor healing; if the degradation is too slow, scar hyperplasia may be caused. In summary, the strength degradation rate and absorbability rate of the traditional Chinese medicine residue-based cellulose formate provided in this application are adjustable, which has a significant impact on wound healing. Among them, the higher the degree of substitution and degree of polymerization, the slower the tissue absorbs the suture, and the longer the degradation time required.
[0009] In addition, the weak acid environment formed by the degradation of cellulose formate in body fluids can inhibit bacterial adhesion and growth, which makes the medical sutures prepared with cellulose formate not only truly absorbable, but also antibacterial and antibacterial (co-cultured with Gram-positive and Gram-negative bacteria for 72 hours, the inhibition rate is greater than 90%), and has great practical application value.
[0010] Preferably, the cellulose formate is prepared by the following steps:
[0011] (1) Sulfonation pretreatment of Chinese medicine residue: Sulfonation pretreatment is performed on the Chinese medicine residue to remove part of hemicellulose and lignin, and obtain a cellulose raw material with a purity greater than 85% and a degree of polymerization greater than 900. The conditions for sulfonation pretreatment are: the amount of Na2SO3 is 10-20% of the mass of the Chinese medicine residue, the amount of saponin is 1-5% of the mass of the Chinese medicine residue, the solid-liquid ratio of the Chinese medicine residue to water is 1:4-1:10, the reaction temperature is 100-150°C, and the reaction time is 1-3h.
[0012] (2) One-pot method for preparing cellulose formate: the cellulose raw material obtained in step (1) is mixed evenly with the formic acid solution, and a formate esterification reaction is carried out under the condition of low-temperature steam explosion treatment to obtain Chinese medicine residue-based cellulose formate; wherein the solid-liquid ratio of cellulose to formic acid solution is 1:1-1:3, and the concentration of formic acid solution is 50-98%. The conditions of the low-temperature steam explosion are: steam explosion pressure 0.1-0.5MPa, and pressure holding time 1-10min. The present application innovatively carries out steam explosion pretreatment and formate esterification reaction simultaneously, which not only promotes the penetration of formic acid in Chinese medicine residue cellulose, improves the esterification efficiency in a short time, and increases the ester substitution degree (1.3-2.5), but also shortens the reaction time, effectively avoids the degradation of cellulose, and allows cellulose to retain a higher degree of polymerization (400-600), and finally obtains cellulose formate that is more conducive to the preparation of absorbable medical sutures - the sutures prepared in this way degrade for 14-49 days under a simulated in vivo environment, and the strength loss is greater than 50%, which is consistent with the wound healing time.
[0013] On the contrary, when the ester substitution degree is lower than 1.3, cellulose formate cannot be completely dissolved in formic acid solution, and its water resistance is low, and the prepared medical suture is very easy to absorb water and degrade (the suture strength loss is greater than 50% within 5 days); and cellulose formate with an ester substitution degree greater than 2.5, due to the excessively severe reaction conditions, causes severe degradation of cellulose (degree of polymerization less than 200), and the strength cannot meet the use requirements of medical sutures.
[0014] A method for preparing a Chinese medicine residue cellulose-based antibacterial and absorbable medical suture, wherein the Chinese medicine residue-based cellulose formate as described above is dissolved in formic acid to obtain a formic acid solution of cellulose formate, i.e., a spinning solution, and then wet spinning and drying are performed to obtain a cellulose formate medical suture. The solid-liquid ratio of the Chinese medicine residue-based cellulose formate to the formic acid solution is 1:20-1:100, and the concentration of the formic acid solution is 80-98%. The wet spinning is performed by using a spinning machine to spray the spinning solution at room temperature and injecting it into a coagulation bath to obtain a wet silk thread, which is then dried to obtain a cellulose medical suture. The drying process is specifically performed by drying the wet silk thread at 30-80°C for 1-10 minutes.
[0015] The cellulose medical suture prepared by the above method has high strength (150-300MPa, knotting strength 80-200MPa, elongation at break 10-30%), excellent antibacterial performance (co-cultured with Gram-positive and Gram-negative bacteria for 72 hours, the antibacterial rate is greater than 90%), degradable and absorbable, and the degradation performance is adjustable (degradation in a simulated in vivo environment for 14-49 days, the tensile strength loss is 50-100%; and in 45-90 days, due to the synergistic effect of water absorption and degradation of the suture and the release of micro-acid, the suture can be gradually converted into glucose that can be absorbed and utilized by human tissue, and the conversion rate is 20-50%). In addition, the cellulose medical suture has excellent biocompatibility, which makes the wound heal faster after suture.
[0016] Preferably, the spinning speed of the wet spinning is 1-50 m / min, the spinneret diameter is 10-50 μm, the coagulation bath uses 1-10 wt% sodium hydroxide solution, the forming time is 10-60 min, and the silk thread is washed with water after forming.
[0017] Beneficial effects of the present invention:
[0018] (1) The present invention first provides a new use of cellulose formate based on traditional Chinese medicine residues as a medical suture. The inventor unexpectedly discovered that the cellulose formate can be degraded into glucose that can be absorbed and utilized by human tissue in simulated body fluids, thereby achieving true absorbability, overcoming the technical bias in the prior art, and achieving unexpected technical effects.
[0019] (2) The Chinese medicine residue-based cellulose formate described in the present invention makes full use of the cellulose in the Chinese medicine residue, which not only reduces the environmental burden and saves the expenditure of pharmaceutical companies in treating waste residues, but also realizes the secondary utilization of resources and increases economic benefits. It is of great significance to promote the green, low-carbon and high-quality development of the Chinese medicine industry.
[0020] (3) The present invention also provides a method for preparing the aforementioned Chinese medicine residue-based cellulose formate, and a method for preparing medical sutures using the Chinese medicine residue-based cellulose formate based on the method, thereby establishing a process for preparing antibacterial and absorbable medical sutures using Chinese medicine residues as raw materials. The process is simple to operate, has mild reaction conditions, low process costs, and good industrial application prospects.
[0021] (4) The medical suture prepared in the present application not only solves the problem that cellulose-based medical sutures in the prior art cannot be absorbed and have no antibacterial properties, but also has good strength, and its degradation time can be adjusted according to the wound healing speed. It also has excellent biocompatibility, which effectively accelerates the wound healing speed and has important social significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Attached Figure 1 This is the preparation process of esterified cellulose using the Chinese medicine Astragalus as raw material in Example 1.
[0023] Attached Figure 2 This is a physical picture of the absorbable medical suture thread made of astragalus residue in Example 1.
[0024] Attached Figure 3 It is the strength loss rate of the Astragalus residue suture in Example 1 during the degradation process.
[0025] Attached Figure 4 It is the change of pH value and glucose conversion rate when the Astragalus residue suture line in Example 1 is degraded (indicating that a trace amount of formic acid is released during degradation, promoting the conversion of cellulose into glucose that can be absorbed by tissues).
[0026] Attached Figure 5 The compatibility of the Astragalus residue suture in Example 1 to HL7702 and MIA-CAPA2 cells.
[0027] Attached Figure 6 This is the preparation process of the medical suture thread with Danshen residue in Example 3.
[0028] Attached Figure 7 This is the inhibitory effect of the Salvia miltiorrhiza residue suture in Example 3 on the growth of Gram-positive and Gram-negative bacteria. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with the embodiments. The feasibility of the present method is further described below through specific implementation examples, but it does not mean that the present invention is limited to these examples.
[0030] The Chinese medicine residue used in the following embodiments is obtained by boiling and filtering the Chinese medicine according to the Chinese medicine boiling method. Specifically, the Chinese medicine is washed and boiled with 10 times the mass of water for 30 minutes. After filtering, the same mass of water is added to the solid residue and boiled. This is repeated three times. The obtained solid residue is the Chinese medicine residue.
[0031] Example 1: Preparation of cellulose-based antibacterial and absorbable medical sutures from Chinese medicine residues
[0032] (1) Sulfonation pretreatment of Chinese herbal medicine residue: Astragalus herbal medicine residue was used as raw material and subjected to sulfonation pretreatment. The pretreatment conditions were as follows: the amount of Na2SO3 was 20% relative to the mass of the Chinese herbal medicine residue, the amount of saponin was 5% of the mass of the Chinese herbal medicine residue, the solid-liquid ratio of the Chinese herbal medicine residue to water was 1:10, the reaction temperature was 150°C, the reaction time was 3 h, and after the reaction, the cellulose raw material with a purity of 91% and a degree of polymerization of 900 was obtained by washing.
[0033] (2) Preparation of cellulose formate by one-pot method: The solid-liquid ratio of cellulose to formic acid solution is 1:3, and the concentration of formic acid solution is 98%. The conditions of low-temperature steam explosion are: steam explosion pressure 0.5 MPa, and pressure holding time 10 min. After the reaction, the cellulose formate obtained has an ester substitution degree of 2.5, a polymerization degree of 400, and a crystal structure of type II.
[0034] (3) Preparation of medical sutures by wet spinning: The solid-liquid ratio of the Chinese medicine residue-based cellulose formate to the formic acid solution is 1:20, and the concentration of the formic acid solution is 80wt%. The spinning speed of the wet spinning is 50m / min, and the spinneret diameter is 50μm; the coagulation bath uses a 1wt% sodium hydroxide solution, the molding time is 60min, and the silk thread is washed with water after molding. The drying process is specifically as follows: drying the wet silk thread at 80°C for 1min, and the Chinese medicine residue-based cellulose formate suture thread can be obtained after drying. The preparation process of the suture thread is as follows Figure 1 As shown in the actual picture Figure 2 shown.
[0035] Through strength testing, the tensile strength of the suture is 300MPa, the elongation at break is 30%, and the knotting strength is 200Mpa (see Table 1 for details). Figure 3 is the strength loss rate of the Astragalus suture prepared in this example during the degradation process. Figure 3 It can be seen that the Astragalus residue suture is degraded in a simulated in vivo environment (phosphate buffer solution, pH 7.2) for 49 days and the tensile strength loss is 50%.
[0036] Attached Figure 4is the change of pH value and glucose conversion rate when the astragalus residue suture prepared in this embodiment is degraded. Figure 4 It can be seen that after 90 days of degradation, the glucose conversion rate of the suture is 20%; at the same time, the pH value of the degradation system decreases from 7.2 to 4.2. The inventors analyzed that this is due to the release of trace amounts of formic acid during the degradation process; and it is precisely the formic acid released during degradation that promotes the conversion of cellulose into glucose that can be absorbed by tissues, making the suture truly absorbable by the human body, solving the technical problem of "only degradation but no absorption" in the prior art.
[0037] Attached Figure 5 The compatibility of the Astragalus residue suture prepared in this example with human liver cells (HL7702) and human pancreatic cancer cells (MIA-CaPa2) is shown in Table 1. Figure 5 It can be seen that after the suture was co-cultured with HL7702 and MIA-CAPA2 cells for 72 hours, the cell survival rates were 91% and 98% respectively, and the hemolysis rate was 3%, indicating that it had no obvious inhibitory effect on cell proliferation, had good biocompatibility, and met the standards for in vivo implant materials (less than 5%).
[0038] Example 2: Preparation of Chinese medicine residue cellulose-based antibacterial, absorbable medical sutures
[0039] Different from Example 1,
[0040] (1) Sulfonation pretreatment of Chinese medicinal residues: Astragalus residues were used as raw materials for sulfonation pretreatment. The pretreatment conditions were as follows: the amount of Na2SO3 was 10% relative to the mass of the Chinese medicinal residues, the amount of saponin was 1% of the mass of the Chinese medicinal residues, the solid-liquid ratio of the Chinese medicinal residues to water was 1:4, the reaction temperature was 100°C, the reaction time was 1 h, and after the reaction, a cellulose raw material with a purity of 85% and a degree of polymerization of 1100 was obtained by washing.
[0041] (2) Preparation of cellulose formate by one-pot method: the cellulose raw material obtained in step (1) is uniformly mixed with the formic acid solution, and formate esterification reaction is carried out under the condition of low-temperature steam explosion treatment, and the cellulose formate based on Chinese medicine residue is washed and air-dried after the reaction to obtain cellulose formate. The solid-liquid ratio of cellulose to formic acid solution is 1:1, and the concentration of formic acid solution is 50%. The conditions of the low-temperature steam explosion are: steam explosion pressure 0.1 MPa, pressure holding time 1 min. After the reaction, the cellulose formate has an ester substitution degree of 1.3, a polymerization degree of 600, and a crystal structure of type II.
[0042] (3) Preparation of medical sutures by wet spinning: dissolving the Chinese medicine residue-based cellulose formate obtained in step (2) in formic acid to obtain a spinning solution, and then wet spinning and drying to prepare the medical sutures. The solid-liquid ratio of the Chinese medicine residue-based cellulose formate to the formic acid solution is 1:100, and the concentration of the formic acid solution is 98wt%. The wet spinning is as follows: spinning the spinning solution with a spinning machine at room temperature, and injecting it into a coagulation bath to obtain a wet silk thread, and then drying to obtain a cellulose medical suture. The spinning speed is 1m / min, and the spinneret diameter is 10μm; the coagulation bath uses a 10wt% sodium hydroxide solution, the molding time is 10min, and the silk thread is washed with water after molding. The drying treatment is specifically as follows: drying the wet silk thread at 30°C for 10min. After drying, the Astragalus residue cellulose formate suture can be obtained.
[0043] Through strength testing, the tensile strength of the suture is 150MPa, the elongation at break is 10%, and the knotting strength is 80MPa.
[0044] Example 3: Preparation of cellulose-based antibacterial and absorbable medical sutures from Chinese medicine residues
[0045] Different from Example 1,
[0046] (1) Sulfonation pretreatment of Chinese medicinal residues: Salvia miltiorrhiza residues were used as raw materials for sulfonation pretreatment. The pretreatment conditions were as follows: the amount of Na2SO3 was 15% relative to the mass of the Chinese medicinal residues, the amount of saponin was 3% of the mass of the Chinese medicinal residues, the solid-liquid ratio of the Chinese medicinal residues to water was 1:6, the reaction temperature was 130°C, the reaction time was 2 h, and after the reaction, a cellulose raw material with a purity of 88% and a degree of polymerization of 980 was obtained by washing.
[0047] (2) Preparation of cellulose formate by one-pot method: The solid-liquid ratio of cellulose to formic acid solution is 1:2, and the concentration of formic acid solution is 80%. The conditions of the low-temperature steam explosion are: steam explosion pressure 0.3 MPa, and pressure holding time 5 min. After the reaction, the cellulose formate obtained has an ester substitution degree of 2.0, a polymerization degree of 420, and a crystal structure of type II.
[0048] (3) Preparation of medical sutures by wet spinning: The solid-liquid ratio of the Chinese medicine residue-based cellulose formate to the formic acid solution is 1:50, and the concentration of the formic acid solution is 85wt%. The spinning speed of the wet spinning is 20m / min, and the spinneret diameter is 30μm; the coagulation bath uses a 5wt% sodium hydroxide solution, the molding time is 30min, and the silk thread is washed with water after molding. The drying process is specifically as follows: drying the wet silk thread at 50°C for 5min. After drying, the Chinese medicine residue-based cellulose formate suture can be obtained. The preparation process of the suture is as follows: Figure 6 shown.
[0049] Attached Figure 7The inhibitory effect of the suture thread made of Danshen medicinal residue in Example 2 on the growth of Gram-positive and Gram-negative bacteria. Figure 7 It can be seen that the antibacterial rates of the suture thread against Gram-positive bacteria and Gram-negative bacteria are 91% and 93% respectively, and the suture thread has excellent antibacterial performance and is helpful for wound healing.
[0050] Example 4: Preparation of cellulose-based antibacterial and absorbable medical sutures from Chinese medicine residues
[0051] Different from Example 1,
[0052] (1) Sulfonation pretreatment of Chinese herbal medicine residue: Pueraria root residue was used as raw material for sulfonation pretreatment. The pretreatment conditions were as follows: the amount of Na2SO3 was 18% relative to the mass of the Chinese herbal medicine residue, the amount of saponin was 2% of the mass of the Chinese herbal medicine residue, the solid-liquid ratio of the Chinese herbal medicine residue to water was 1:8, the reaction temperature was 140°C, the reaction time was 1.5 h, and after the reaction, the cellulose raw material with a purity of 90% and a degree of polymerization of 1000 was obtained by washing.
[0053] (2) Preparation of cellulose formate by one-pot method: The solid-liquid ratio of cellulose to formic acid solution is 1:3, and the concentration of formic acid solution is 95%. The conditions of low-temperature steam explosion are: steam explosion pressure 0.4 MPa, and pressure holding time 8 min. After the reaction, the cellulose formate obtained has an ester substitution degree of 1.8, a polymerization degree of 550, and a crystal structure of type II.
[0054] (3) Preparation of medical sutures by wet spinning: The solid-liquid ratio of the Chinese medicine residue-based cellulose formate to the formic acid solution is 1:80, and the concentration of the formic acid solution is 90wt%. The spinning speed of the wet spinning is 4m / min, and the spinneret diameter is 20μm; the coagulation bath uses a 2wt% sodium hydroxide solution, the molding time is 50min, and the silk thread is washed with water after molding. The drying treatment is specifically: drying the wet silk thread at 70°C for 2min. After drying, the Chinese medicine residue cellulose formate suture thread can be obtained.
[0055] Example 5: Preparation of cellulose-based antibacterial and absorbable medical sutures from Chinese medicine residues
[0056] Different from Example 1,
[0057] (1) Sulfonation pretreatment of Chinese medicinal residues: The residues of Codonopsis pilosula were used as raw materials for sulfonation pretreatment. The pretreatment conditions were as follows: the amount of Na2SO3 was 11% relative to the mass of the Chinese medicinal residues, the amount of saponin was 4% of the mass of the Chinese medicinal residues, the solid-liquid ratio of the Chinese medicinal residues to water was 1:5, the reaction temperature was 110°C, the reaction time was 2.5 h, and after the reaction, a cellulose raw material with a purity of 87% and a degree of polymerization of 1050 was obtained by washing.
[0058] (2) Preparation of cellulose formate by one-pot method: The solid-liquid ratio of cellulose to formic acid solution is 1:3, and the concentration of formic acid solution is 60%. The conditions of low-temperature steam explosion are: steam explosion pressure 0.2 MPa, and pressure holding time 2 min. After the reaction, the cellulose formate obtained has an ester substitution degree of 1.4, a polymerization degree of 500, and a crystal structure of type II.
[0059] (3) Preparation of medical sutures by wet spinning: The solid-liquid ratio of the Chinese medicine residue-based cellulose formate to the formic acid solution is 1:40, and the concentration of the formic acid solution is 95wt%. The spinning speed of the wet spinning is 40m / min, and the spinneret diameter is 15μm; the coagulation bath uses an 8wt% sodium hydroxide solution, the molding time is 20min, and the silk thread is washed with water after molding. The drying treatment is specifically: drying the wet silk thread at 40°C for 10min. After drying, the Chinese medicine residue cellulose formate suture thread can be obtained.
[0060] Comparative Example 1: Example in which low-temperature steam explosion treatment and formate esterification reaction are carried out separately
[0061] Different from Example 1, the astragalus cellulose raw material in Example (1) is first subjected to low-temperature steam explosion treatment, and the conditions for low-temperature steam explosion are: the solid-liquid ratio of cellulose raw material to water is 1:3, the steam explosion pressure is 0.5 MPa, and the pressure holding time is 10 minutes. Subsequently, the raw material after explosion treatment is subjected to formate esterification reaction, and the reaction conditions are: the solid-liquid ratio of cellulose to formic acid solution is 1:50 (cellulose content exceeding this ratio will result in it not being well dispersed in formic acid, the system has no fluidity, and the reaction uniformity is poor), the concentration of formic acid solution is 98%, the esterification temperature is 30°C, and the time is 10 hours. After the reaction, the cellulose formate is obtained by washing.
[0062] After the reaction, the cellulose formate obtained has an ester substitution degree of 0.15, a degree of polymerization of 1300, and a type I crystal structure. Due to the low degree of substitution of cellulose formate, it cannot be dissolved in formic acid (a degree of substitution lower than 1.3 cannot be dissolved in formic acid) to obtain a uniform spinning solution, and thus cellulose formate yarn cannot be obtained by wet spinning. This shows that the present application adopts a one-pot method to prepare cellulose formate - steam explosion pretreatment and formate esterification reaction are carried out simultaneously, which not only saves the process flow, shortens the reaction time, and reduces production costs, but also promotes the penetration of formic acid in traditional Chinese medicine residue cellulose, improves the esterification efficiency in a short time, and increases the ester substitution degree (1.3), and obtains cellulose formate that can be dissolved in formic acid solution, producing unexpected technical effects.
[0063] Example 6: Performance test of Chinese medicine residue-based cellulose formate suture
[0064] The performance of the traditional Chinese medicine residue-based cellulose formate sutures prepared in Examples 1-5 was tested and compared with commercially available collagen absorbable medical sutures. The results are shown in Table 1. The commercially available collagen absorbable medical sutures (diameter 7-0) were manufactured by Shandong Boda Company. The specific test method is as follows:
[0065] (1) Test of sample degree of polymerization
[0066] The degree of polymerization (DP) of the Chinese medicine residues and esterified cellulose samples was tested using the capillary viscometer method according to the international ISO 5351 / 1 standard.
[0067] (2) Degree of substitution test
[0068] 0.3 g of freeze-dried esterified cellulose sample was added to 30 mL of 50% ethanol solution, wherein the ethanol solution contained 0.2 M sodium hydroxide. The suspension was stirred at room temperature for 24 h, and then 30 mL of 0.2 M hydrochloric acid solution was added. After 30 min, the suspension was titrated with 0.1 M sodium hydroxide solution using phenolphthalein as an indicator. The sulfonated traditional Chinese medicine residue was also tested as a blank sample according to the same procedure. The formyl content of the esterified cellulose sample was calculated using formula (1), and then the ester substitution degree (DS) of the sample was calculated using formula (2).
[0069]
[0070]
[0071] Among them, V B (mL) is the volume of sodium hydroxide required for the blank sample titration, V s (mL) is the volume of sodium hydroxide required to titrate the esterified cellulose sample, N NaOH is the equivalent concentration of sodium hydroxide solution, M formyl is the molecular weight of the formyl group (29 g / mol), W (g) is the mass of the sample used, and 162 is the molecular weight of the anhydroglucose unit.
[0072] (3) Testing of antibacterial properties of sutures
[0073] (a) Culture medium preparation: LB liquid medium (100 mL distilled water + 2.5 g LB broth medium, sterilized at 121°C for 15 min), LB solid medium (100 mL distilled water + 2.5 g LB broth medium + 1.5 g agar powder, sterilized at 121°C for 15 min, then 15 mL was poured into a sterile plate).
[0074] (b) Preparation of bacterial suspension: Take three 12 mL bacterial culture tubes, add 3 mL LB liquid medium to each tube, pick single colonies from the solid culture medium of Staphylococcus aureus and Escherichia coli and add them to the liquid culture medium, and use the other tube as a blank control. Place in a constant temperature shaker (37°C, 200 rpm) and shake culture overnight (15 h).
[0075] (c) Sample processing: 10 mg of Chinese medicine residue-based suture samples were weighed and placed in 15 mL centrifuge tubes according to the groups. The tubes were sterilized in a high-temperature and high-pressure steam sterilizer at 121° C. for 20 min and set aside.
[0076] (d) Co-culture and plate spread count test: The bacterial solution was diluted to 10 using LB liquid medium. 6 CFU / mL, add 1mL of diluted bacteria to the sample tubes respectively, and add no sample to the control group. Place in a 37℃ constant temperature incubator and shake for 24h. After the culture is completed, dilute the bacterial solution 10 times continuously with sterile PBS solution, take 100μL of the dilution and evenly spread it on LB solid culture medium. Place in a 37℃ constant temperature incubator and culture for 18h, take out and take pictures and record the number of colonies.
[0077] (4) Cytocompatibility testing
[0078] The CCK-8 (cell counting kit-8) test method was used to analyze the cell compatibility of Chinese medicine residue-based medical sutures on human hepatocytes (HL7702) and human pancreatic cancer cells (MIA-CaPa2). Specific steps:
[0079] (a) A certain concentration of cell suspension was pre-cultured, and then ultraviolet-sterilized silk threads were added and cultured at 37°C for 72 h.
[0080] (b) Add CCK-8 solution to the cell culture plate and continue incubation for 1 h;
[0081] (c) The absorbance of each well at 450 nm (OD value, As) was measured using an ELISA reader, and the cell viability was calculated using formula (1), wherein the wells without silk thread and cells were used as blanks (Ab), and the wells without silk thread samples were used as controls (Ac).
[0082]
[0083] (5) Strength loss rate / absorbability test
[0084] In order to simulate the strength loss of Chinese medicine residue-based medical sutures in vivo, PBS buffer (pH 7.2) was selected as the in vivo degradation environment, and the dried sutures were immersed in a buffer of 10 times the mass. After a period of time, the sutures were taken out, the strength of the sutures was tested, and the strength loss rate was calculated. At the same time, the absorbability of the sutures was evaluated by the glucose conversion rate. The specific method was as follows: 1.5 mL of PBS buffer filtered by a microporous membrane was taken, the amount of glucose was analyzed by liquid chromatography, and the glucose conversion rate of the sutures was calculated.
[0085] (6) Hemolysis rate test
[0086] Take 8mL of fresh anticoagulated blood and dilute it with 10mL of normal saline. Add 0.2mL of diluted blood to 10mL of distilled water as a positive control, and add 0.2mL of diluted blood to 10mL of normal saline as a negative control. Wash the clean silk thread with an appropriate amount of distilled water twice and place it in a test tube. Add 10mL of distilled water to each tube, keep it in a 37℃ constant temperature box for 30min, add 0.2mL of diluted blood, mix gently and continue to keep warm for 60min, centrifuge for 5min (centrifugal force 750×g), draw the supernatant into a cuvette, and measure the absorbance A value at a wavelength of 545nm with a spectrophotometer. The operation of the positive control and the negative control (without adding silk thread) is the same as above. If the hemolysis rate of the silk thread is <5%, it meets the requirements of the in vivo implant material; >5% shows that the silk thread has a hemolytic effect and is not suitable as an in vivo implant material.
[0087]
[0088] Table 1. Results of performance tests of traditional Chinese medicine residue-based sutures prepared in Examples 1-5 and commercially available products
[0089]
[0090] From Table 1, we can see that:
[0091] (1) Mechanical properties: The strength of the Chinese medicine residue-based sutures prepared in Examples 1-5 of the present application is 150-300 MPa, the knotting strength is 80-200 MPa, and the elongation at break is 10-30%. The strength of the commercially available collagen absorbable medical suture (Shandong Boda Company) is 200 MPa, the knotting strength is 90 MPa, and the elongation at break is 29%. It can be seen that the mechanical properties of the Chinese medicine residue-based sutures prepared in Examples 1-5 of the present application are comparable to those of the commercially available collagen absorbable medical sutures, and even the tensile strength and knotting strength can be significantly improved.
[0092] (2) Antibacterial performance: When the culture time is 72 hours, the antibacterial rates of the Chinese medicine residue-based sutures prepared in Examples 1-5 of the present application against Gram-positive bacteria and Gram-negative bacteria are 91-95% and 92-97%, respectively. However, the commercially available collagen absorbable medical sutures have no antibacterial properties against Gram-positive bacteria, and the antibacterial rate against Gram-negative bacteria is only 38%. This shows that the antibacterial performance of the Chinese medicine residue-based sutures prepared in Examples 1-5 of the present application is significantly better than that of the commercially available collagen absorbable medical sutures.
[0093] (3) Degradation performance: In a simulated body fluid environment of phosphate buffer solution (pH 7.2), the Chinese medicine residue-based sutures prepared in Examples 1-5 of the present application degraded for 14-49 days, and the tensile strength loss was 50% ( Figure 3 ); and degrades for 45-90 days, the suture gradually converts into glucose that can be absorbed and utilized by human tissues, with a conversion rate of 20-50% ( Figure 4 ). The commercially available collagen absorbable medical sutures degraded for 7 days and lost 50% of their tensile strength. Since their degradation products are amino acids, they cannot be evaluated by glucose conversion rate.
[0094] This shows that the Chinese medicine residue-based sutures prepared in Examples 1-5 of the present application not only have the properties of being degradable and absorbable, but more importantly, by adjusting the ester substitution degree (1.3-2.5) and polymerization degree (400-600) of cellulose formate, their degradation time can be regulated over a longer time range to match the healing time of different wounds, thereby contributing to the healing of wounds and having important social significance.
[0095] (4) Implant material performance: After the Chinese medicine residue-based sutures prepared in Examples 1-5 of the present application were co-cultured with human hepatocytes (HL7702) or human pancreatic cancer cells (MIA-CaPa2) for 72 hours, the cell survival rate was greater than 91% ( Figure 5 ), and the hemolysis rate was 3-4%, which meets the standards for in vivo implant materials (less than 5%). After 72 hours of co-culture of commercially available collagen absorbable medical sutures with human hepatocytes (HL7702), the cell survival rate was 98%, and the hemolysis rate was 3.5%. This shows that the suture prepared by the present invention has no obvious inhibitory effect on cell proliferation, has excellent cell compatibility, and is comparable to commercially available products, meets the standards for medical in vivo implant materials, and is expected to be used as absorbable medical sutures on a large scale.
[0096] In summary, the Chinese medicine residue-based cellulose formate sutures prepared by the method described in the present application have the following advantages: (1) The various mechanical property data are comparable to or even significantly improved compared to commercially available collagen absorbable medical sutures, and the antibacterial performance is significantly better than commercially available collagen absorbable medical sutures. (2) The Chinese medicine residue-based cellulose formate sutures described in the present application are not only truly "absorbable and degradable", but also by adjusting the ester substitution degree (1.3-2.5) and polymerization degree (400-600) of cellulose formate, their degradation time can be regulated within a longer time range to match the healing time of different wounds. (3) The sutures prepared by the present invention have no obvious inhibitory effect on cell proliferation, have excellent cell compatibility, and are comparable to commercially available products, meeting the standards for medical in vivo implant materials.
[0097] Therefore, the present invention not only provides a new use of Chinese medicine residue-based cellulose formate as a truly "absorbable and degradable" medical suture, overcomes the technical bias in the prior art, and achieves unexpected technical effects; it also makes full use of the cellulose in Chinese medicine residues, which is of great significance for promoting the green, low-carbon and high-quality development of the Chinese medicine industry. At the same time, the preparation method provided by this application is not only simple to operate, mild in reaction conditions, and low in process cost, but also has product performance comparable to or even better than that of commercially available products, with good industrial application prospects and great social significance.
Claims
1. An application of Chinese medicine residue-based cellulose formate as medical suture, characterized in that: The cellulose formate is separated from traditional Chinese medicine residues; the ester substitution degree of the cellulose formate is 1.3-2.5, the crystal form is cellulose II type, and the polymerization degree is 400-600.
2. The use according to claim 1, characterized in that: The cellulose formate is prepared by the following steps: (1) Sulfonation pretreatment of Chinese medicine residue: Sulfonation pretreatment is performed on the Chinese medicine residue to remove part of the hemicellulose and lignin, and obtain a cellulose raw material with a purity greater than 85% and a degree of polymerization greater than 900; (2) One-pot method for preparing cellulose formate: the cellulose raw material obtained in step (1) is uniformly mixed with a formic acid solution, and then subjected to a formic acid esterification reaction under low-temperature steam explosion treatment conditions to obtain Chinese medicine residue-based cellulose formate; wherein the solid-liquid ratio of cellulose to formic acid solution is 1:1-1:3, and the concentration of the formic acid solution is 50-98%.
3. The use according to claim 2, characterized in that: The conditions of the sulfonation pretreatment in step (1) are as follows: the amount of Na2SO3 is 10-20% of the mass of the Chinese medicine residue, the amount of saponin is 1-5% of the mass of the Chinese medicine residue, the solid-liquid ratio of the Chinese medicine residue to water is 1:4-1:10, the reaction temperature is 100-150°C, and the reaction time is 1-3h.
4. The use according to claim 2, characterized in that: The conditions of the low-temperature steam explosion in step (2) are: steam explosion pressure 0.1-0.5 MPa, and pressure holding time 1-10 min.
5. The use according to any one of claims 1 to 4, characterized in that: The Chinese medicine residue raw materials are one or more of astragalus, codonopsis, atractylodes, angelica, ligusticum chuanxiong, polygonatum, dipsaccharum, pueraria, rhodiola, salvia miltiorrhiza, rehmannia root and coptis root.
6. A method for preparing a cellulose-based antibacterial, absorbable medical suture made from traditional Chinese medicine residues, characterized in that: The Chinese medicine residue-based cellulose formate as claimed in any one of claims 1 to 5 is dissolved in formic acid to obtain a formic acid solution of cellulose formate, i.e., a spinning solution, and then wet spinning and drying are performed to prepare Chinese medicine residue-based cellulose formate medical sutures.
7. The preparation method according to claim 6, characterized in that: The solid-liquid ratio of the traditional Chinese medicine residue-based cellulose formate to the formic acid solution is 1:20-1:100, and the concentration of the formic acid solution is 80-98%.
8. The preparation method according to claim 7, characterized in that: The wet spinning method comprises the following steps: using a spinning machine to spray the spinning solution at room temperature and injecting the spinning solution into a coagulation bath to obtain wet silk thread, and then drying the wet silk thread to obtain the Chinese medicine residue-based cellulose formate medical suture thread; wherein the spinning speed of the wet spinning method is 1-50 m / min, and the spinneret hole diameter is 10-50 μm.
9. The preparation method according to claim 8, characterized in that: The coagulation bath uses a 1-10wt% sodium hydroxide solution, the molding time is 10-60 minutes, and the silk thread is washed with water after being formed.
10. The preparation method according to any one of claims 6 to 9, characterized in that: The drying treatment in step (3) is specifically as follows: drying the wet silk thread at 30-80° C. for 1-10 min.